(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
The present study aimed to analyze in the literature the technologies implemented to prevent pressure injuries in the context of hospital care. This is an integrative literature review carried out from October to December 2021, in the databases: Virtual Health Library; MEDLINE via PubMed; Scopus; Web of Science; Embase and Cochrane Library, and 192 articles were included and 179 excluded. The final sample consisted of 13 articles, that met the eligibility criteria and answered the objective and research question. The main technologies used were air mattresses, permanent education mediated by e-learning, a computer system that facilitates the identification of risk factors, a light signal system for activating the team, a computer system for monitoring tissue pressure, a software for implementing computerized guidelines, an informative catalog, clinical guidelines, and a virtual learning environment. These technologies have shown positive results, however, as identified in the analysis, most studies deal with descriptive research designs with low inference power, which opens space for experimental research to prove the real benefits of technologies more accurately for pressure injury prevention.